1998
DOI: 10.1046/j.1365-2036.1998.00419.x
|View full text |Cite
|
Sign up to set email alerts
|

Gastro‐oesophageal reflux associated with nocturnal gastric acid breakthrough on proton pump inhibitors

Abstract: Nocturnal acid breakthrough is frequently seen on proton pump inhibitors twice daily and is often accompanied by oesophageal reflux. This has important implications for medical therapy in patients with severe gastro-oesophageal reflux and Barrett's oesophagus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
133
1
4

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(146 citation statements)
references
References 10 publications
8
133
1
4
Order By: Relevance
“…The initial salivary pH is correlated with pH in the lower esophagus and is higher in GER subjects than in control subjects (8). In addition, Katz et al (9) ORIGINAL A nocturnal decline of salivary pH associated with airway hyperresponsiveness in asthma Naoto Burioka 1 , and Eiji Shimizu detected nocturnal gastric acid breakthrough (NAB), defined as nighttime periods exceeding 1 h with a gastric pH below 4.0, in 67% of normal subjects ; and it was previously reported that there is a nocturnal decline of salivary pH in healthy subjects (10). Saliva is an important determinant of esophageal acid neutralization in patients with NAB as well as in GER patients (8).…”
Section: Introductionmentioning
confidence: 99%
“…The initial salivary pH is correlated with pH in the lower esophagus and is higher in GER subjects than in control subjects (8). In addition, Katz et al (9) ORIGINAL A nocturnal decline of salivary pH associated with airway hyperresponsiveness in asthma Naoto Burioka 1 , and Eiji Shimizu detected nocturnal gastric acid breakthrough (NAB), defined as nighttime periods exceeding 1 h with a gastric pH below 4.0, in 67% of normal subjects ; and it was previously reported that there is a nocturnal decline of salivary pH in healthy subjects (10). Saliva is an important determinant of esophageal acid neutralization in patients with NAB as well as in GER patients (8).…”
Section: Introductionmentioning
confidence: 99%
“…17 NAB was as high as 90% in patients taking once daily omeprazole in one study. 4 Katz et al 5 showed that NAB occurred in 70% of patients with GERD while taking twice daily omeprazole. 5 Similar results were shown by other studies as well using twice daily omeprazole.…”
Section: Discussionmentioning
confidence: 99%
“…4 Katz et al 5 showed that NAB occurred in 70% of patients with GERD while taking twice daily omeprazole. 5 Similar results were shown by other studies as well using twice daily omeprazole. [18][19][20]21 On the contrary, one of our previous studies showed lower frequency of NAB among patients taking once daily omeprazole, though the number of patients studied was less than that in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nocturnal acid breakthrough does occur in a subset of patients, but will usually be controlled by an evening dose of proton pump inhibitor. 15 Unfortunately, H 2 RAs, whilst initially effective in reducing nocturnal acid, typically are subject to the development of tolerance. An alternative approach is to prescribe an H 2 RA on an as-needed basis before bedtime, to assist with night-time symptomatology.…”
Section: What To Do If Long-term Management Failsmentioning
confidence: 99%